Analysis of the technology acceptance model in evaluating students’ perspective towards the use of Zankoline system - Shareef M. Shareef; Hazha Saeed Yahia (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The development and utilization of technology has motives the society’s dependence on Information and Communication Technology (ICT). One of technology variants is the zankoline system, which is described as the use of services through the internet. In which it’s an eservice system which provides access to students to apply for the region’s universities for the undergraduate studies. The research aims to analyze the technology acceptance model (TAM) in order to evaluate students’ perspectives towards the use of Zankoline system. The total of 200 forms was distributed and 140 survey response rate was received. Elements that were evaluated comprised of perceived usefulness, perceived ease of use, and intention to use. The collected data were analyzed using SPSS based on the TAM technique via hypothesis test. The findings revealed that the research participants' perspectives were low regarding the use of zankoline system, this is due to the most of the research participants were not applied to the zankoline and were accepted through direct admission.